2012
DOI: 10.1128/jvi.06706-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus (HMPV) Binding and Infection Are Mediated by Interactions between the HMPV Fusion Protein and Heparan Sulfate

Abstract: bHuman metapneumovirus (HMPV) is a major worldwide respiratory pathogen that causes acute upper and lower respiratory tract disease. The mechanism by which this virus recognizes and gains access to its target cell is still largely unknown. In this study, we addressed the initial steps in virus binding and infection and found that the first binding partner for HMPV is heparan sulfate (HS). While wild-type CHO-K1 cells are permissive to HMPV infection, mutant cell lines lacking the ability to synthesize glycosam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 71 publications
3
117
1
Order By: Relevance
“…Consistent with this, recombinant hMPVs carrying these mutations replicated as efficiently as wild- type hMPV in cell culture and in cotton rats. Previously, it was shown that virus with the D331A mutation retains approximately 80% of fusion activity (25), which was consistent with our observation. In addition, we found that rhMPV-D331A was defective in viral replication in cell culture and cotton rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with this, recombinant hMPVs carrying these mutations replicated as efficiently as wild- type hMPV in cell culture and in cotton rats. Previously, it was shown that virus with the D331A mutation retains approximately 80% of fusion activity (25), which was consistent with our observation. In addition, we found that rhMPV-D331A was defective in viral replication in cell culture and cotton rats.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Chang et al (2012) suggested that heparan sulfate proteoglycans may function as the primary receptor for hMPV F protein (25). Mutant CHO cell lines lacking the ability to synthesize glycosaminoglycans (GAGs), particularly heparan sulfate proteoglycans, were resistant to hMPV binding and infection, although wild-type CHO-K1 cells were permissive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For viruses in the Paramyxovirinae subfamily, it is firmly established that membrane fusion requires a specific interaction between two glycoproteins, the attachment protein (HN, H, or G) and the fusion (F) protein (1,9,14,15,23,39), and such fusion occurs at neutral pH (4,27). Specifically, it is thought that the binding of the attachment protein to cell surface receptors triggers major conformational changes in F, which in turn activates membrane fusion (1,27,29,30,39).However, membrane fusion of pneumoviruses appears to be unique among the paramyxoviruses, in that fusion is accomplished by the F protein alone without help from the attachment glycoprotein (6,7,17,21,42,43). This suggests that the F proteins of pneumoviruses possess dual functions, receptor binding and fusion promotion.…”
mentioning
confidence: 99%